Penerapan Metode Six Sigma dalam Pencegahan dan Pengendalian Infeksi di Rumah Sakit: A Systematic Review - Waluyo Waluyo; Sholihin Sholihin; Roby Aji Permana; Tria Anisa Firmanti; Yulia Indah Permatasari (FORIKES, 2020)
Background: Prevention and control of infections is a priority in the current health sector, and prevention of infection is an indicator of the quality of services provided. Purpose: to examine the available evidence about the application of the Six Sigma method in the prevention and control of infections in hospitals. Method: The database used to identify suitable articles obtained from Scopus, Pubmed, Ebscohost and Summon was limited to the last 5 years of publication from 2014 to 2019, English, and fulltext articles. The literature review used the keyword